“Streets of menace” - Murray Lee; Mark Halsey; Asher Flynn (Oñati Socio-Legal Series)
This paper explores the symbolic and instrumental impacts associated with labelling particular groups of young people as perpetrators of organised gang activity. Using case studies from two Australian cities, we point primarily to the constitutive and damaging nature of much media and public discourse about youth gang crime and show how young offenders’ disadvantage and disenfranchisement is rendered largely invisible or immaterial to understanding the causes and solutions to such problems. In an era of “fake news”, social media “echo chambers”, civil conflict, mass international migration / forced diasporas, as well as the reassertion of strong sovereign borders, we ask: how might one de-escalate the “monstering” of young people whose identity (and presence and place in society) is known primarily, if not exclusively, through the “noise” and visibility of their offending?